An assessment of knowledge, attitude, and practice of video gaming and the relationship with depression among university students - Abdul Ghani, Radiah; Salleh, Anisa (UPM Press, 2022)
Introduction: Video games which are electronic games played on a video screen, has the potential to be one of the leading causes of depression among youth. Since there are only few studies on the issue, this study identified the level of knowledge, attitude, and practice (KAP) on the effects of video gaming on depression among International Islamic University Malaysia (IIUM) students and the correlation between them. Methods: A self-developed question-naire, with four sections on socio-demographic characteristics, knowledge, attitude and practice on depression and video games, was used to do a cross-sectional survey among 140 IIUM students. The level of KAP was evaluated using a descriptive frequency table. Pearson correlation test was used to determine the correlation. Results: The majority of the respondents had moderate level of knowledge (56.4%) and attitude (57.1%). For practice scores, the majority portrayed a poor level of it (73.6%). Only knowledge and attitude scores showed positive correlation (r = 0.440). Conclusion: This study showed that increasing knowledge on factors of excessive video gaming habits and factors that increases the risk for development of depression can be helpful in tackling the rising rate of depression among the youth in Malaysia.